Single living in the opinion of young adults - Urbańska, Magda (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
One of the dimensions of modern family transformation is an increase in the attractiveness of alternative forms of family life, including being alone as a single person, without a life partner. Until recently, living without a spouse was treated as a life failure, currently it is more often viewed as deliberate choice of this form of life, associated with independence, freedom, living one’s own life. Social perception of people being single is changing, which is also reflected in the results of the author’s own research.
Keywords: living single; family